Awareness and knowledge of endo-perio lesions among fifth year students and interns at King Saud Dental College: a questionnaire-based study - Almadi, Khalid Hamad; Bin Akresh, Abdulrahman Ibrahim; Fahad Abushaqqaf, Hisham; Assiry, Yazeed Ahmed; Almefyaz, Musaad Ibrahim; Alghamdi, Ayoub Abdullah; Alnutaifi, Abdulrahman Abdullah (International Journal Of Community Medicine And Public Health, 2023)
Background: This study aims to assess the diagnostic knowledge and understanding of endo-perio lesions among senior dental students and interns enrolled at King Saud College of Dentistry. Methods: A cross-sectional questionnaire-based study was conducted using Google Forms. The questionnaire included two radiographic case images and assessed participants’ experience with endo-perio lesions, confidence in diagnosis, and familiarity with treatment approaches. The study included 200 participants, consisting of 140 interns and 60 5th-year students. Results: The majority of participants (61%) reported encountering endo-perio lesions in their clinics. Among the participants, 50% expressed confidence in diagnosing these lesions. Intern students demonstrated higher knowledge and awareness of endo-perio lesions compared to 5th-year students. Statistically significant differences were observed in the awareness of endo-perio lesions and confidence in diagnosis between the two groups. However, both groups showed room for improvement in their diagnostic and treatment capabilities. Conclusions: The findings indicate a need for enhanced education and training in this area, particularly for 5th-year students. Incorporating comprehensive theoretical education, clinical case management, and continuing education courses may help improve students’ diagnostic skills and treatment outcomes for endo-perio lesions.